8 - Homeownership Intention among Igbo Ethnic Group in Ilorin: Olusegun F. Liadi & Aisha Sanusi Tapamose - Olusegun F. Liadi; Aisha Sanusi Tapamose (African Sociological Review, 2021)
The extant literature has previously shown that attitude towards homeownership and pressure from reference groups may significantly affect individual’s homeownership intention especially in many western societies. The authors assumed that Nigerian citizens might also have similar experience especially for non-indigenes living and working in states in geo-political zones outside their own ethnic areas. The study surveyed 300 members of Igbo ethnic group residents in Ilorin metropolis. Simple random sampling method was adopted and data was gathered through structured questionnaire. The authors questioned participants about their attitude and intention towards owning personal home in the city. They also asked participants to relate to questions about the perceived easiness to acquire properties for personal use in the city and about the social (families’ and relatives’) pressure on their homeownership intention. Analytical techniques include simple frequency and percentage distributions, pearson chi-square and independent t-test. Research findings show that while many sampled participants have positive attitude towards homeownership in Ilorin, length of stay in the city, level of education and the perceived control affect homeownership intention among the participants. A surprising result was that subjective norms appear to exert little or no influence on participants’ homeownership intention. Hence, the finding demonstrates the interactive nature of social influence/personal norms dimension in homeownership through availability of and access to information and sources of homeownership funding.